Wilson's disease - clinical picture, factors influencing disease progression, treatment methods - Monika Korga; Paweł Pawlik; Przemysław Zaroda; Jakub Wawrzkowicz; Patrycja Niewinna; Paweł Dąda; Dominika Mańdziuk; Michał Żuchowski; Klaudia Kołodziej; Wojciech Kołodziej (Nicolaus Copernicus University in Toruń, 2024)
Wilson's disease, also known as hepatolenticular degeneration, is a rare genetic metabolic disorder that leads to excessive accumulation of copper in the body, particularly in the liver and brain. This results in the gradual damage of these organs and leads to a variety of clinical symptoms. The symptoms of Wilson's disease can be diverse, leading to a broad spectrum of clinical manifestations including fatigue, jaundice, hand tremors, mood disorders, difficulty walking, speech disturbances, as well as neurological and psychiatric issues.The treatment of Wilson's disease typically involves the oral administration of copper-chelating agents, which help the body to eliminate the excess copper. In some cases, symptomatic treatment related to liver or brain damage may also be necessary. The diagnosis of Wilson's disease is based on laboratory tests, imaging studies (such as MRI or CT scans), and the assessment of clinical symptoms. Due to the variety of symptoms, patients are often misdiagnosed, and untreated Wilson's disease inevitably leads to death. Genetic testing can also be useful in confirming the diagnosis. Although Wilson's disease is a chronic condition, with appropriate treatment and monitoring, its symptoms can be effectively managed, and further damage to the liver and brain can be prevented. Regular monitoring of copper levels in the blood, as well as liver and brain function, is crucial for the effective management of Wilson's disease.